Surgery for Locally Recurrent Rectal Cancer: Tips, Tricks, and Pitfalls - Warrier, Satish K.; Heriot, Alexander G.; Lynch, Andrew Craig (Clinics in Colon and Rectal Surgery, 2016)
Rectal cancer can recur locally in up to 10% of the patients who undergo definitive resection for their primary cancer. Surgical salvage is considered appropriate in the curative setting as well as select cases with palliative intent. Disease-free survival following salvage resection is dependent upon achieving an R0 resection margin. A clear understanding of applied surgical anatomy, appropriate preoperative planning, and a multidisciplinary approach to aggressive soft tissue, bony, and vascular resection with appropriate reconstruction is necessary. Technical tips, tricks, and pitfalls that may assist in managing these cancers are discussed and the roles of additional boost radiation and intraoperative radiation therapy in the management of such cancers are also discussed.
Keywords: pelvic exenteration; rectal cancer; cancer recurrence; colorectal surgery